Array comparative genomic hybridization analysis identified the chromosomal aberrations and putative genes involved in prostate tumorigenesis of Malaysian men - Nenny Noorina Saaid; Reena Rahayu Md. Zin; Siti Aishah Md Ali; Sharifah Noor Akmal Syed Hussain; Zulkifli Zainuddin; Zubaidah Zakaria (Universiti Kebangsaan Malaysia, 2014)
The identification of chromosomal aberrations in prostate cancer has been widely studied with several known oncogenes and tumor suppressor genes have successfully been discovered. The most frequent aberrations detected in western population were losses in chromosome 5q, 6q, 8p, 13q, 16q, 17p, 18q and gains of 7p/q and 8q. The purpose of this study was to determine the chromosomal aberrations among Malaysian men of Southeast Asia population and discover those potential genes within that chromosomal aberrant region. Thirty-six formalin-fixed paraffin embedded specimens consist of eight organ-confined prostate cancer cases, five with capsular invasion, 14 showed metastasis and nine cases had no tumor stage recorded, were analyzed by array CGH technique. Chromosomal losses were frequently detected at 4q, 6q, 8p, 13q, 18q while gains at 7q, 11q, 12p, 16q and 17q. Gain of 16q24.3 was statistically significant with tumor size. Gains of 6q25.1 and Xq12 as well as losses of 3p13-p1.2 and 13q33.1-q33.3 were significantly correlated with Gleason grade whereas 12p13.31 gain was associated with bone metastasis. Several potential genes have also been found within that aberrant region which is myopodin (4q26-q27), ROBO1 (3p13-p11.2), ERCC5 (13q33.1-q33.3) and CD9 (12p13.31), suggesting that these genes may play a role in prostate cancer progression. The chromosomal aberrations identified by array CGH analysis could provide important clues to discover potential genes associated with prostate tumorigenesis of Malaysian men.